Evaluation of clogging resistance, strength, and durability in high-strength pervious concrete with recycled concrete aggregate, sustainable binder, and hydrophobic treatments - Trinh Nhat Ho Tran; Harsimranpreet Kaur; Chai Jaturapitakkul; Montakan Senalohit; Mang Tia; Jian Zou; Weerachart Tangchirapat (Journal of Materials Research and Technology)
This study investigated high-strength pervious concrete (HSPC) containing recycled concrete aggregate (RCA) of two sizes including large (9.5–12.5 mm) and small (4.75–9.5 mm). Ultra-high-performance mortar (UHPM) was employed to enhance the interface transition zone between the mortar matrix and RCA. A novel approach using sustainable binder replacements, including high-volume ground bottom ash (GBA), fly ash (FA), and calcium stearate (CS), was adopted. HSPC mixtures were evaluated for compressive strength, void ratio, permeability, water absorption ratio (WAR), clogging resistance, water contact angle, and microstructural properties using scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), and X-ray diffraction (XRD). The achieved results revealed that replacing binder with CS decreased density and reduced compressive strength by 8-23%. The CS formed an overhydrophobic or superhydrophobic coating with a water contact angle of 140–150°, maintaining permeability above 1 mm/s after five clogging cycles. HSPC with 10% CS and small RCA exhibited a WAR of 0.09-0.77 mm, significantly lower than HSPC without CS. The XRD confirmed that CS released calcium ions, promoting additional C–S–H formation. The SEM revealed increased porosity in CS-modified paste, contributing to reduced compressive strength. The EDS indicated reduced calcium (Ca) and silicon (Si) contents, suggesting reactions between CS derived calcium ions and SiO2 in GBA and FA. These findings highlight the potential of CS-modified HSPC to achieve clogging resistance while maintaining acceptable permeability, despite reduced strength. These findings indicated the potential for CS-modified HSPC to provide clogging resistance.